The "madness" of market logic: mental illness and late capitalism in The Double and Nightcrawler. Issue 1 (2nd January 2017) - Brayton, Sean
ABSTRACT: This paper examines representations of mental illness in popular film, particularly Richard Ayoade's The Double and Dan Gilroy's Nightcrawler . As I argue, both films trouble typical Hollywood narratives of mental illness by situating schizophrenia and psychopathy, for instance, within a socioeconomic context, specifically relations of production under late capitalism and the unfettered self-interest of neoliberalism. If mental illness is a product of the postindustrial workplace in The Double, it becomes a prerequisite for success in Nightcrawler, providing a cinematic depiction of mental illness at odds with the "personal pathology" paradigm that dominates the current neoliberal landscape.